Economic and social characterization of the community aqueducts of Villavicencio 2018 (Revista "Boletín el Conuco", 2024)
The Operation and Maintenance of Water Supply Systems - water management in transboundary basins carried out by the International Union, mentions “that an aqueduct is one that collects water from the catchment source that can be a source, either a well or a river and carries it through pipes, to each of the houses” (Sanabria, 2010), whose purpose is to supply those people who do not have water in each of their homes and thus be able to carry out each of their activities. Having said the above, an investigation is carried out, which focuses on the economic and social study of the community aqueducts of the city of Villavicencio. In addition, it considers the importance of building a document that contains information about the current state of community aqueducts and their contribution to the development of communities.
Keywords: Community aqueduct; water; common good; human development; homes; public services